From script to stage in early modern England - Holland, Peter (Palgrave Macmillan, 2004)
This collection brings together a group of distinguished and original theater historians engaged in rethinking the nature of early modern theater history as a discipline. Whether focusing on the relation between scripts and performance practice, the structure of theatrical companies, the social dimensions of drama, or the archaeology of the stage, all are concerned with basic questions of evidence and interpretation, and offer significant, and often startling, revisions of our view of the early modern theater.